APPLICATION OF THE KAMPALA TRAUMA SCORE VERSUS INJURY SEVERITY SCORE IN PREDICTING MORTALITY AMONG ROAD TRAFFIC ACCIDENT VICTIMS IN THE EMERGENCY DEPARTMENT (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Road traffic accidents are a major cause of trauma-related morbidity and mortality. Early identification of patients at risk of death is essential in emergency departments to guide triage, resuscitation, referral, and definitive care. The Kampala Trauma Score (KTS) is a simple clinical scoring system based on physiological and injury-related parameters, whereas the Injury Severity Score (ISS) is an anatomical score based on injury severity across body regions. Aim: To compare the predictive performance of KTS and ISS for mortality among road traffic accident victims presenting to the emergency department during 2022–2023. Materials and Methods: This retrospective observational study included road traffic accident victims managed in the emergency department from January 2022 to December 2023. Demographic data, road-user category, arrival time, physiological status, injury pattern, KTS, ISS, and mortality outcome were recorded. Predictive performance was assessed using receiver operating characteristic curve analysis, sensitivity, specificity, positive predictive value, negative predictive value, diagnostic accuracy, and multivariable logistic regression. Results: A total of 356 patients were included, and mortality was recorded in 41 patients (11.5%). Non-survivors were older and more frequently had delayed arrival, hypotension, altered sensorium, ICU admission, surgical intervention, head and neck injury, chest injury, abdominal/pelvic injury, and polytrauma. KTS showed an area under the curve of 0.845, while ISS showed an area under the curve of 0.869. KTS demonstrated higher specificity and diagnostic accuracy, whereas ISS showed higher sensitivity. Conclusion: Both KTS and ISS showed good mortality discrimination. KTS is useful for rapid bedside triage, while ISS remains valuable for anatomical severity assessment and trauma outcome reporting.